Tax Governance in the Era of Pillar Two: Legal Certainty, Risk Management, and Strategic Responses in Indonesia - Achaddiah, Bella Noer (Yayasan Sinergi Kawula Muda, 2025)
This study analyzes Indonesia’s implementation of the global minimum tax under PMK 136/2024, which adopts the OECD Pillar Two framework establishing a 15% minimum effective tax rate for multinational enterprises (MNEs). The research aims to evaluate compliance implications, strategic adjustments, and governance challenges faced by MNEs under this regime. Using a qualitative approach that integrates literature review, comparative regulatory analysis, and thematic interpretation of professional insights, the study assesses Indonesia’s legal framework, OECD guidelines, and professional commentaries to examine legal certainty, compliance obligations, and strategic tax responses. Findings indicate that PMK 136/2024 increases administrative complexity, particularly in managing GloBE Information Returns, calculating jurisdictional effective tax rates, and reconciling reporting data. Transitional measures such as safe harbours and SBIE carve-outs provide limited relief but demand strong internal governance. Legal ambiguities and administrative capacity gaps create compliance risks, including delays in GIR submissions, errors in ETR computation, and potential penalties. The study concludes that Indonesia’s adoption of the global minimum tax represents a major policy shift toward international tax harmonization. However, successful implementation depends on clear regulatory guidance, enhanced digital infrastructure, and strengthened institutional capacity. The findings provide actionable insights for policymakers and corporate leaders in navigating the evolving landscape of global tax reform.